-910=n6

Rewrite the equation as n6=-910.

n6=-910

Multiply both sides of the equation by 6.

6⋅n6=6⋅-910

Cancel the common factor of 6.

Cancel the common factor.

6⋅n6=6⋅-910

Rewrite the expression.

n=6⋅-910

n=6⋅-910

Simplify 6⋅-910.

Cancel the common factor of 2.

Factor 2 out of 6.

n=2(3)⋅-910

Factor 2 out of 10.

n=2⋅3⋅-92⋅5

Cancel the common factor.

n=2⋅3⋅-92⋅5

Rewrite the expression.

n=3⋅-95

n=3⋅-95

Combine 3 and -95.

n=3⋅-95

Simplify the expression.

Multiply 3 by -9.

n=-275

Move the negative in front of the fraction.

n=-275

n=-275

n=-275

n=-275

Solve using the Square Root Property -9/10=n/6